Implementasi Polmas Untuk Mencegah Tindak Pidana Pencurian Kendaraan Bermotor Roda Dua - Yulliasmi, Cut (Indonesian Journal of Police Studies, 2020)
This research is based on the implementation of police duty on the Binmas function in dealing with criminal acts of the two-wheeled curanmor that occurred in the jurisdiction of Bogor police. The aim of the study was to find out the criminal act of the wheels and the implementation of Polmas in preventing criminal acts of the second wheel curanmor at the Bogor police. The authors use research libraries and conceptual literature. The theory and concepts used are management theory, SWOT analysis, the concept of prevention, Polmas concept, and Perkap No. 3 year 2015. This research uses a qualitative approach, with the field method reseach (field research). The data collection techniques used are interviews, observations and document studies. Technical analysis of data through data reduction, data serving and withdrawal of conclusions. The author conducts research for the analysis of curanmor criminal acts, the implementation of Polmas in preventing criminal acts of the second wheel curanmor in Bogor police. The implementation of POLMAS activities not in accordance with SOP Karna is influenced by several factors. The arrival of Bhabinkamtibmas members to the community makes an awkward society because they imagine police as opposed to them. In fact, Bhabinkamtibmas members aim to give the appeal and call for Harkamtibmas. The results showed that Polmas has been implemented by BHABINKAMTIBMAS members but not optimal. Bogor Police has also carried out several activities routinely conducted by Bhabinkamtibmas namely Sambang, siskamling, Polmas, FGD (Forum Group Discussion) with village head, community leaders and religious figures. Based on the results of the study, the author advised to provide routine vocational or training education to Bhabinkamtibmas to increase the insight and improvement of the member's ability of Binmas.